2022
DOI: 10.1038/s41598-022-24794-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the benefits of reducing synthetic nitrogen application policy on ecosystem carbon sequestration and biodiversity

Abstract: Synthetic Nitrogen (N) usage in agriculture has greatly increased food supply over the past century. However, the intensive use of N fertilizer is nevertheless the source of numerous environmental issues and remains a major challenge for policymakers to understand, measure, and quantify the interactions and trade-offs between ecosystem carbon and terrestrial biodiversity loss. In this study, we investigate the impacts of a public policy scenario that aims to halve N fertilizer application across European Union… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Over the last four decades, the use of synthetic nitrogen (N) fertilizer in the world's agricultural industry has increased sharply for feeding the increasing world population [1]. However, about 50% of the applied N leaks from the agro-production system through ammonia (NH 3 ) volatilization, nitrous oxide (N 2 O) emissions, and nitrate (NO 3 − ) leaching [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last four decades, the use of synthetic nitrogen (N) fertilizer in the world's agricultural industry has increased sharply for feeding the increasing world population [1]. However, about 50% of the applied N leaks from the agro-production system through ammonia (NH 3 ) volatilization, nitrous oxide (N 2 O) emissions, and nitrate (NO 3 − ) leaching [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Our primary focus is to analyze the consequences for agricultural production, prices, land use changes, and GHG emissions at both local (EU) and global levels. Other aspects, such as biodiversity and carbon impacts, have been explored in (Devaraju et al, 2022), and a summary of the policy effects can be found in a related publication (Prudhomme et al, 2022).…”
mentioning
confidence: 99%